Association of hyperactivated transposon expression with exacerbated immune activation in systemic lupus erythematosus - Frank Qingyun Wang; Xiao Dang; Huidong Su; Yao Lei; Chun Hing She; Caicai Zhang; Xinxin Chen; Xingtian Yang; Jing Yang; Hong Feng; Wanling Yang (Mobile DNA)
Abstract Background Systemic Lupus Erythematosus (SLE) is a complex autoimmune disorder, and transposable elements (TEs) have been hypothesized to play a significant role in its development. However, limited research has explored this connection. Our study aimed to examine the relationship between TE expression and SLE pathogenesis. Methods We analyzed whole blood RNA-seq datasets from 198 SLE patients and 84 healthy controls. The REdiscoverTE pipeline was employed to quantify TE and other gene expressions, identifying differentially expressed TEs. A TE score was calculated to measure overall TE expression for each sample. Gene ontology and gene set enrichment analyses were conducted to explore the functional implications of TE upregulation. Independent datasets were utilized to replicate the results and investigate cell type-specific TE expression. Results Our analysis identified two distinct patient groups: one with high TE expression and another with TE expression comparable to controls. Patients with high TE expression exhibited upregulation of pathways involving nucleic acid sensors, and TE expression was strongly correlated with interferon (IFN) signatures. Furthermore, these patients displayed deregulated cell composition, including increased neutrophils and decreased regulatory T cells. Neutrophils were suggested as the primary source of TE expression, contributing to IFN production. Conclusions Our findings suggest that TE expression may serve as a crucial mediator in maintaining the activation of interferon pathways, acting as an endogenous source of nucleic acid stimulators in SLE patients.